(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Early Childhood Caries (ECC) is a global public health concern. This study aimed to assess parental perception and practice regarding ECC among patients attending Pedodontics departments of selected tertiary hospitals. Materials and methods: This cross-sectional study involved 233 parent-child pairs visiting Pedodontics Departments at Chattagram International Dental College Hospital and Chittagong Medical College Hospital. The study included parents having children under 6 years of age. Data were collected through a pre-tested semi- structured questionnaire, and face-to-face interviews were conducted. The sampling technique used was purposive. Ethical clearance was obtained from the Institutional Review Board of Chattagram International Dental College. Results: In this study, 75% of children had a self-brushing habit, parental supervision during brushing was irregular in about 50% of cases. More than 50% of parents were unaware that long-term bottle-feeding can contribute to the development of tooth decay. In this study, 75.5% of children had decayed teeth. About 80% of parents frequently missed to clean their child’s teeth. There was a significant relationship between the presence of decayed teeth in the child and the perception of parents regarding prolonged bottle feeding can help to develop caries (p<.009). Conclusion: This study reveals inadequate parental perception and practice concerning early childhood oral health. It emphasizes the necessity for parental education through oral health promotional programs. JCMCTA 2025 ; 36 (1) : 159-163